헬스케어 제품의 컬러 트렌드 분석 - 주대원(Joo, Deh Won) (한국디자인리서치, 2022)
본 연구의 목적은 iF Design Award를 수상한 최근 4년간의 헬스케어 제품을 중심으로 컬러 트렌드를 조사하여 먼셀 H V/C 분포와 색조합 유형별 특징을 파악함으로써 신제품을 디자인할 때 기초자료로 활용할 수 있도록 하는데 있다. 이를 위해 2018년부터 2021년까지 총 365제품을 일반 헬스케어 제품군과 메디컬 제품군으로 나누어 컬러 트렌드를 분석하였다. 컬러의 분석 방법은 iF Design Award 웹사이트에 있는 제품 사진을 색채관리 소프트웨어로 먼셀 H V/C를 추출하여 먼셀 챠트에 분포시키는 과정으로 진행되었다. 색상은 난색계열, 한색계열, 중성색계열로 분류하였고 명도와 채도는 각각 세 그룹으로 나누어 컬러 트렌드의 변화를 파악하였다. 색조합 유형별 분석은 15가지 유형으로 세분화하여 빈도를 추출하고 일반 헬스케어 제품군과 메디컬 제품군 간의 공통점과 차이점을 분석하였다. 최종 도출된 컬러 트렌드의 경향은 크게 세 가지로 요약된다. 첫째, 두 그룹의 헬스케어 제품은 공통적으로 하양(N9.5)과 검정(N1), PB와 B색상, YR과 R색상의 빈도가 높았으며 고명도와 중명도의 빈도가 지속적으로 강세를 유지하고 있었고, 고채도와 저채도의 비율이 높게 나타나고 있음을 확인하였다. 둘째, 일반 헬스케어 제품군의 경우 무채색(하양, 검정, 회색) 배색이 꾸준히 강세를 유지하고 있고 사용자 친화적인 난색계열의 배색이 지속되는 경향을 보였다. 셋째, 메디컬 제품군의 특징은 한색계열이 난색계열보다 10~11% 높은 빈도를 보이고 있고, 한색계열을 중심으로 중-고-저명도와 고채도 영역의 확대가 나타나는 특징이 있다. 이것은 사용자들에게 안정감과 신뢰감을 주어야 하는 메디컬 제품의 특성을 잘 반영하는 것으로 해석된다. The purpose of this study is to investigate the color trend focusing on healthcare products that have won the iF Design Award for the past 4 years, and to understand the Munsell H V/C distribution and the characteristics of each color combination type, so it is used as basic data when designing new products. To this end, we analyzed color trends by dividing a total of 365 products from 2018 to 2021 into general healthcare products and medical products. The color analysis method was carried out according to the process of extracting Munsell H V/C with color management software from product photos on the iF Design Awards website and plotting them on the Munsell chart. Colors (hue) were classified into warm colors, cold colors, and neutral colors. Then, the change in color trend was identified by dividing the value and chroma into three groups. For color combination type analysis, the frequency was extracted by subdividing into 15 types, and the similarities and differences between the general healthcare product group and the medical product group were analyzed. The final derivative of color trends can be summarized into three main categories. First, the health products of the two groups had high frequencies of white (N9.5) and black (N1), PB and B colors, and YR and R colors in common, and the frequencies of high and median values continued to be strong. Also, it was confirmed that the ratio of high chroma to low chroma was high. Second, in the case of general healthcare products, achromatic (white, black, gray) color schemes were consistently strong, and the user-friendly combination of warm colors showed a tendency to continue. Third, the characteristic of medical product group is that cold colors show 10~11% higher frequency more than warm colors. It is characterized by expanding the high-middle-low values and high-saturation areas with a focus on the cold color series. This is interpreted as reflecting the characteristics of medical products that should give users a sense of stability and trust. KCI Citation Count: 0